Analysis of Sale and Buy Practices in A Review of Sharia Economic Law: (Study on China Market in Bone Regency) - Syahruddin Kadir (el-Uqud: Jurnal Kajian Hukum Ekonomi Syariah, 2023)
The practice of buying and selling which has become the primary activity carried out by the community is still not free from fraud and tyranny. The injustice committed by traders or sellers is to show good merchandise and hide merchandise that is not good or defective. Of course, this causes harm to every buyer or consumer, even though Muslims must know that this behavior is strictly prohibited by religion. This study aims to determine the buying and selling practices practiced by the people in the China market in Bone Regency and to find out the sharia economic system implemented by the people in the China market in Bone Regency. Bone. This research method uses field research like the field through data collection namely observation, interviews, and questionnaires. Direct research examines buying and selling practices carried out by the Muslim community at the China Market in Bone Regency, running like a market as it should be. The China market includes markets that carry out buying and selling transactions through the sale of crops from farmers which are obtained directly from the initial farmers. Apart from that, it is also a center for the wholesale trade of plantation, plantation, and fishery products as well as other basic needs. Fraud and tyranny that occurred in the China market and unbalanced market conditions should not have happened because it is prohibited in Islam. This phenomenon shows a violation of Islamic values ​​and law which has strictly prohibited all forms of tyranny and fraud in buying and selling activities so the sharia economic system in the China market has not been implemented optimally.